Agronomic performance of pearl millet genotypes under variable phosphorus, water, and environmental regimes. Issue 1 (16th December 2020) - Halilou, Oumarou; Assefa, Yared; Falalou, Hamidou; Abdou, Harou; Achirou, Bacharou F.; Karami, Sadissou M. A.; Jagadish, S. V. Krishna
Abstract: Water and P deficiency can significantly limit pearl millet [ Pennisetum glaucum (L.) R. Br.] productivity and response to N application in the arid and semi‐arid regions of Africa. The objectives of this research were to quantify the responses of improved pearl millet genotypes and a landrace to contrasting rainfall gradient and P deficient soil conditions across different locations in Niger. The study was conducted at four locations: (a) Tara, (b) the International Crop Research Institute for the Semi‐Arid Tropics (ICRISAT) research station at Sadoré, (c) Maradi, and (d) Araourayé, Niger, during 2015 and 2016 rainy seasons. Results of the study indicated that the effect of P fertilizer application on shoot weight, panicle weight, grain yield, and harvest index was different by environment (year × location). As high as 113% straw yield, 72% panicle weight, and 100% grain yield advantage was obtained with P application over low P in favorable environments. Across all genotypes and in both P treatments, irrigation had a consistent effect on the agronomic performance. On average, there was significantly greater straw yield (629 vs. 492 g m –2 ), panicle weight (472 vs. 229 g m –2 ), grain yield (257 vs. 122 g m –2 ), and harvest index (0.25 vs. 0.15) in the irrigated site compared with rainfed sites. Among the tested genotypes, Mil de Siaka showed relatively consistent performance in irrigated, water deficit, and P deficient conditions, emerging as an ideal candidate for inclusion into pearl millet breeding programs, aimed toward developing multi‐stress tolerant pearl millet varieties.